Storytelling Digital Lewat Vlog Sebagai Media Rebranding Basuki Tjahaja Purnama - Alan Dermawan (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2021)
ABSTRACT After being released from prison for the blasphemy case, politician Basuki Tjahaja Purnama backs on politic and rebuilding his reputation. Using the vlog as a medium, Basuki presents a new personality which is more positive and friendly, so that the public can forget his negative image in the past. This study aims to identify storytelling in Basuki's vlog as a form of rebranding activities he undertakes. The research method was carried out through literature studies and by descriptive analysis techniques. Data collection techniques were carried out using thirteen vlogs on “Panggil Saya BTP” Youtube channel. The results showed that Basuki consistently displayed rebranding activities through storytelling in vlogs. The rebranding activity was carried out by Basuki with new name, new logo, and new slogan, which was carried out to erase the negative image of his past. The construction of positive impressions was carried out by Basuki in the vlog through storytelling both explicitly through content and explicitly through gestures, although there was a lack of technical storyplotting elements. The presence of Basuki on Youtube can be one example of the successful adoption of new media in political communication conducted by politicians after experiencing a reputation crisis. Keywords: Political Branding, Rebranding, Storytelling, Vlog